Geographic Information Systems in the context of disabilities (Journal of Accessibility and Design for All, 2018)
The importance of geographical space for persons with disabilities is elaborated in literature through numerous papers on ‘geographies of disabilities’, dealing with the social construction and impact of space. Space is identified as an enabling factor to enhance self-determination and independence e.g. in terms of social participation, mobility or access. Geographic Information Systems (GIS) can be utilized to visualise and analyse the spatial impact of human actions. Research on GIS applications for disability issues shows a variety of approaches through disciplines and topics but lacks a comprehensive assessment of potentials. The objective of this paper is to provide a synopsis of research results and practical approaches of GIS applications in disability-related contexts. Methods applied include a qualitative literature review of scientific papers, proceedings, projects and case studies using digital databases (e.g. ScienceDirect, JSTOR etc.). Based on the review an overview on target groups, core functionalities of GIS, the purpose of application was extracted. A SWOT analysis was used to stress strengths and weaknesses to identify gaps and future research areas. The review has shown that GIS for space-related disability issues is established in various disciplines with a diversity of topics. Focus is given to mapping and identifying accessibility, wayfinding tools supporting orientation and navigation next to disaster and emergency management support. Major constraints for the use of GIS are the availability, accuracy and costs of data, addressing single target groups/disabilities (e.g. users of wheelchairs) and the usability/transferability of applications. To exploit the full potential of GIS in disability studies, emphasis can be given to research on implementation of additional data sources, on integrating the inclusive approach by inter- and transdisciplinary research as well as on transferring good practice examples. The enhancement of GIS in disability studies can contribute to higher autonomy for people with disabilities and foster inclusion in our society.